Predictive validity of the Short-Term Assessment of Risk and Treatability (START) for multiple adverse outcomes: The effect of diagnosis. (October 2017) - Marriott, Rebecca; O'Shea, Laura E.; Picchioni, Marco M.; Dickens, Geoffrey L.
Abstract: The Short-Term Assessment of Risk and Treatability (START) assists risk assessment for seven risk outcomes based on scoring of risk and protective factors and assignment of clinically-informed risk levels. Its predictive validity for violence and self-harm has been established in males with schizophrenia, but accuracy across pathologically diverse samples is unknown. Routine START assessments and 3-month risk outcome data of N = 527 adult, inpatients in a UK secure mental health facility were collected. The sample was divided into diagnostic groups; predictive validity was established using receiver operating characteristics regression (rocreg) analysis in which potential covariates were controlled. In most single-diagnosis groups START risk factors ('vulnerabilities'), protective factors ('strengths'), and clinically-informed estimates predicted multiple risk outcomes with effect sizes similar to previous research. Self-harm was not predicted among patients with an organic diagnosis. The START risk estimates predicted physical aggression in all diagnostic groups, and verbal aggression, self-harm and self-neglect in most diagnostic groups. The START can assist assessment of aggressive, self-harm, and self-neglect across a range of diagnostic groups. Further research with larger sample sizes of those with multiple diagnoses is required. Highlights: Inpatients present multiple risks: assessments should be valid across diverse diagnostic groups. We compared predictive accuracy of the START across multiple diagnostic groups. The tool was supported to an extent but cannot be recommended for use unreservedly. Clinicians should consider evidence for their patient group when assessing risk.